Comparison of sedation scores and propofol induction doses in dogs after intramuscular premedication with butorphanol and either dexmedetomidine or medetomidine. (25th July 2013) - Raszplewicz, Joanna; MacFarlane, Paul; West, Eleanor
Abstract: Objective: To compare sedation scores and propofol induction doses in dogs receiving either dexmedetomidine or medetomidine, both with butorphanol intramuscularly (IM) prior to general anaesthesia. Study design: Prospective, 'blinded', randomized, clinical study. Animals: Fifty client‐owned dogs scheduled for elective diagnostic imaging procedures. Methods: Dogs were allocated to receive butorphanol 0.1 mg kg −1 with either medetomidine (group M) 0.01 mg kg −1 or dexmedetomidine (group D) 0.005 mg kg −1 IM. Sedation was scored before and 20 minutes after pre‐anaesthetic medication using a composite simple descriptive sedation score giving a score of 0 to 15 (0 = no sedation; 15 = profound sedation). Forty‐five minutes after pre‐anaesthetic medication, propofol was administered in increments of 0.5 mg kg −1 over 15 seconds until tracheal intubation was possible. The time required to check intubation conditions between each propofol aliquot was 15 seconds. Total propofol dose required to perform tracheal intubation and the number of dogs achieving a clinically desired sedation score of ≥9/15 was recorded in each group. Sedation score and propofol dose were compared using the Mann‐Whitney U ‐test. Results are reported as median (range). Statistical significance was set at p  < 0.05. Results: The sedation score 20 minutes after pre‐anaesthetic medication was significantly higher in group M [11 (2–14)] than in group D [7 (0–14)]. There was no significant difference between propofol dose requirements in group M [1.5 (1–2.5) mg kg −1 ] or D at [1.5 (1–3) mg kg −1 ]. Significantly more dogs in group M achieved a sedation score of ≥9/15 than in group D. Conclusions and clinical relevance: Combined IM with butorphanol, medetomidine 0.01 mg kg −1 produced effective sedation more frequently than dexmedetomidine 0.005 mg kg −1 in dogs undergoing sedation prior to anaesthesia for elective procedures but this did not affect the propofol dose required for induction of anaesthesia significantly.